Landmarks in Nigerian Labour Law - Odumosu, O. I. (Obafemi Awolowo University Press, 2013)
The contractual relationship between the employer and the employee (master and servant) is crucial for the meaningful operation of a system of collective bargaining. Equally important is the existence of strong trade union organisations whose membership depends on workers who are "job-holders". We have discussed at length these various aspects of our Labour Law in order to shed light on their merits and demerits. The superiority of the employer vis-a-vis his employee looms large in the whole of their employment relationship. The employer has the power to lock-out his workers and his liability to pay wages for the period of lockout and the grant to the workers concerned of continuity of employment do not appear to be a sufficient deterrent. Closely related to this is the whole range of disciplinary powers such as suspension or dismissal, which the employer exercises at will. And, unless the employee is one of the few ones protected by legal status, his only remedy will be claimed for damages.